Three-dimensional cell culture of human mesenchymal stem cells in nanofibrillar cellulose hydrogels. (11th August 2017) - Azoidis, Ioannis; Metcalfe, Joel; Reynolds, James; Keeton, Shirley; Hakki, Sema S.; Sheard, Jonathan; Widera, Darius
Abstract: Abstract : Human mesenchymal stem cells (MSCs) are the most intensely studied and clinically used adult stem cell type. Conventional long-term cultivation of MSCs as a monolayer is known to result in a reduction of their functionality and viability. In addition, large volumes of cell culture medium are required to obtain cell quantities needed for their clinical use. In this proof of concept study, we cultivated human MSCs within a three-dimensional nanofibrillar cellulose (NFC) hydrogel. We show that NFC is biocompatible with human MSCs, and represents a feasible approach to upscaling of their culture.